¡Vuelve Sebastiana! : (los Chipayas) - Beltrán, Luis Ramiro; Kespi, Sebastiana (Bolivia Films LTDA., 1952)
Sebastiana Kespi, a pastoral girl, goes into the forbidden neighboring town, that of the Aymaras. Her grandfather seeks her, trying to convince her to return to his village. --